Can You Really Trust Your Personal Banking Advisor? How Loans with Currency Clause in Swiss Francs Impoverished Croatian Middle Class Households - Rodik, Petra (2012)
In Croatia, there has been a period of intensive expansion of the number of credit loans during 2000-2007 period. Because of the economic crisis, many people nowadays got stuck with huge, barely payable debts. One of the most extreme case is the one of the households with credit loans with currency clauses in Swiss Francs (75000 of them have longterm housing loans). Because of the currency clause and high interest rates, their monthly loan payments artificially increased by an average of 51%. It is not surprising, therefore, that respondents, in the open-ended question where they described their experiences themselves, often state that they feel tricked by banks, unprotected by the government, and fear for the future (unemployment in Croatia has risen sharply from the mid 2009 onwards). So the question that has to be answered is: besides of the obvious flaws of the legal and political framework that allowed this to happen, what were the practices of the banks themselves that have lead to this? One possible answer lays within the concept of trust. As etimology of the word says (latin credo = to believe) credit loan contracting exists on the premise of mutual trust. Banks have hugely exploited this in their marketing of the 'credit products', and people made decision based on the 'expert advice' of their 'personal banking advisors' (bank staff). It is the conclusion of this paper that not only banking operation in Croatia regarding CHF loans was socially irresponible, it was also completely against the fundamental logic of the credit banking itself – it broke the premise of trust.